2022
DOI: 10.1136/rmdopen-2021-001901
|View full text |Cite|
|
Sign up to set email alerts
|

Safety, patient acceptance and diagnostic accuracy of ultrasound core needle biopsy of parotid or submandibular glands in primary Sjögren’s syndrome with suspected salivary gland lymphoma

Abstract: BackgroundEnlargement of the major salivary glands (SGs) is a major risk factor for B-cell lymphoma among patients with primary Sjögren’s syndrome (pSS). Ultrasound-guided core needle biopsy (US-guided CNB) could be a novel technique to manage SG enlargement among patients with pSS.ObjectiveAccordingly, this study’s main aim was to evaluate the safety, patient tolerance and diagnostic accuracy of US-guided CNB procedure for patients with pSS with major SG enlargement.MethodsPatients with clinical diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“… 94 Despite the theoretical risk of facial nerve injury and other complications, when properly performed, a CNB of major SGs may determine transient adverse reactions, with no permanent complications. 19 , 94 , 95 Therefore, US-guided CNB of the SGs can be considered a safe, feasible, and accurate technique in patients with pSS.
Figure 10 Several approaches to US-guided CNB of the parotid and submandibular glands.
…”
Section: Core Needle Biopsy (Cnb)mentioning
confidence: 99%
“… 94 Despite the theoretical risk of facial nerve injury and other complications, when properly performed, a CNB of major SGs may determine transient adverse reactions, with no permanent complications. 19 , 94 , 95 Therefore, US-guided CNB of the SGs can be considered a safe, feasible, and accurate technique in patients with pSS.
Figure 10 Several approaches to US-guided CNB of the parotid and submandibular glands.
…”
Section: Core Needle Biopsy (Cnb)mentioning
confidence: 99%
“…Recently, we proposed the use of ultrasound-guided CNB (US-guided CNB) of the parotid gland for the diagnosis of glandular lymphoma in this subset of pSS with PSW. We demonstrated that US-guided CNB can provide adequate sampling for histological examination, immunohistochemical staining and flow cytometry (16,18). In the case of PSW, this procedure can be safely performed in the posterocaudal part of the gland, in a safe zone where facial nerve injuries are avoided.…”
Section: Feasibility Of Studying the Parotid Glands In Pssmentioning
confidence: 91%
“…In the case of PSW, this procedure can be safely performed in the posterocaudal part of the gland, in a safe zone where facial nerve injuries are avoided. Additional investigation with promising results on the accuracy and safety of US-guided CNB, parotid or submandibular, and in the parotid "safe zone", i.e., also independently from the presence of PSW, are now completed by our group (16,18). The correct disease diagnosis, the relevance and the choice of SGUS glandular areas in disease follow-up, and the analysis in detail of SGUS focal and diffuse areas, with particular reference to lymphoma and its risk, have been planned in larger and multicentric cohorts.…”
Section: Feasibility Of Studying the Parotid Glands In Pssmentioning
confidence: 98%
See 2 more Smart Citations